2020
DOI: 10.1093/condor/duz064
|View full text |Cite
|
Sign up to set email alerts
|

Habitat transformation and climate change: Implications for the distribution, population status, and colony extinction of Southern Bald Ibis (Geronticus calvus) in southern Africa

Abstract: Habitat transformation and loss is one of the greatest threats currently facing avian species. The cumulative impact of climate change on habitat loss is projected to produce disproportionate risk for endemic high-altitude species. The Southern Bald Ibis (Geronticus calvus) is an endemic high-altitude species found throughout highland grassland habitats in South Africa and Lesotho. The historical distribution has contracted notably and causal factors remain ambiguous. Furthermore, the historical population (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Future geographical distribution might be related to the tolerance to a wide range of climatic conditions that facilitates the occupation of large geographic areas (Atauchi et al, 2020;Freeman et al, 2019;Slatyer et al, 2013). Although range-restricted species are predicted to be more vulnerable to global warming (Colyn et al, 2020;Urban, 2015), our results showed that the effects of climate change are not restricted to rangerestricted or habitat specialist species (Dirnb€ ock et al, 2011;Malcolm et al, 2006), and depends on multiple factors, as shown for A. y. yucatanensis and A. y. chalconota. In this study, the subspecies with strong cinnamon coloration (A. y. yucatanensis) showed the highest increase in future distribution area, while the predicted area for the subspecies with less cinnamon coloration (A. y. chalconota) decreased in all future climate-change scenarios.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Future geographical distribution might be related to the tolerance to a wide range of climatic conditions that facilitates the occupation of large geographic areas (Atauchi et al, 2020;Freeman et al, 2019;Slatyer et al, 2013). Although range-restricted species are predicted to be more vulnerable to global warming (Colyn et al, 2020;Urban, 2015), our results showed that the effects of climate change are not restricted to rangerestricted or habitat specialist species (Dirnb€ ock et al, 2011;Malcolm et al, 2006), and depends on multiple factors, as shown for A. y. yucatanensis and A. y. chalconota. In this study, the subspecies with strong cinnamon coloration (A. y. yucatanensis) showed the highest increase in future distribution area, while the predicted area for the subspecies with less cinnamon coloration (A. y. chalconota) decreased in all future climate-change scenarios.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies have evaluated the effects to climate change on current distribution of bird species and showed that the potential distributions in some species is reduced (Atauchi et al, 2020; Knudsen et al, 2011), expand northwards (Hitch & Leberg, 2007; Lara et al, 2012), shifted and contracted when exacerbated by habitat loss (Colyn et al, 2020), and in some cases the impacts of climate change on current distributions of birds were minimal, particularly in range-restricted species (Freeman et al, 2019; Lara et al, 2012). Hummingbirds, as pollinators, are often immersed in highly dependent interactions with plants (Correa-Lima et al, 2019; Ornelas et al, 2004), and constitute the most diverse ensemble of specialized nectarivorous birds in the Americas (Sonne et al, 2016; Zanata et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…hunting is not permitted. In this manuscript we do not consider ne scale spatial modelling as conducted by Colyn et al (2020). In that study, declines in areas of occupancy (AOO) are evident due to encroachment by invasive alien vegetation and loss of grassland habitat.…”
Section: Discussionmentioning
confidence: 99%
“…The Southern Bald Ibis Geronticus calvus is a cliff-nesting species of the Threskiornithidae family, with a range restricted to the grassland biome of South Africa, Lesotho and Eswatini (Henderson 2015). This species favours high-altitude mesic grasslands and agricultural lands with high rainfall and rugged terrain, without the encroachment of trees, shrubs, and bushes (Henderson 2015;Colyn et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation